2012
DOI: 10.1038/ni.2393
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Hobit is a homolog of the transcriptional repressor Blimp-1 that regulates NKT cell effector differentiation

Abstract: The transcriptional repressor Blimp-1 mediates the terminal differentiation of many cell types, including T cells. Here we identified Hobit (Znf683) as a previously unrecognized homolog of Blimp-1 that was specifically expressed in mouse natural killer T cells (NKT cells). Through studies of Hobit-deficient mice, we found that Hobit was essential for the formation of mature thymic NKT cells. In the periphery, Hobit repressed the accumulation of interferon-γ (IFN-γ)-producing NK1.1(lo) NKT cells at steady state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 41 publications
7
94
1
Order By: Relevance
“…The proapoptotic phenotype could also under the control of other transcription factors in combination with PLZF, such as Hobit, which was recently shown to be involved in the terminal differentiation of iNKT cells. 33 We also found that the proapoptotic phenotype of iNKT cells is shared by MAIT cells, the second invariant T-cell lineage in humans. 7 Both populations share developmental, functional, and phenotypical features and are considered as innate-like T lymphocytes.…”
Section: Discussionmentioning
confidence: 68%
“…The proapoptotic phenotype could also under the control of other transcription factors in combination with PLZF, such as Hobit, which was recently shown to be involved in the terminal differentiation of iNKT cells. 33 We also found that the proapoptotic phenotype of iNKT cells is shared by MAIT cells, the second invariant T-cell lineage in humans. 7 Both populations share developmental, functional, and phenotypical features and are considered as innate-like T lymphocytes.…”
Section: Discussionmentioning
confidence: 68%
“…25) Granzyme B is produced by CD8+, NK and NKT cells, and induces apoptosis in tumor cells. [26][27][28][29] The increase in granzyme B in the lymph nodes by Z-100 in the present study suggests that Z-100 may induce apoptosis of tumor cells in lymph nodes by enhancing granzyme B production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that human iNKT cells do harbor some NK-like cytolytic molecules, including granzyme and perforin (20), and a recent study has identified HOBIT (homolog of Blimp-1 in T cells, Znf683) as a transcriptional program for granzyme in mature iNKT cells that have returned back to thymus but not spleen or liver (7). Therefore, we next investigated how iNKT cells mediate the spirochete cell death and observed a Ca 2+ -dependent killing mechanism (EGTA inhibitable) (Fig.…”
Section: Resultsmentioning
confidence: 99%